Report of the Saithe (Coalfish) Working Group ... - ICES (ICES Expert Group reports (until 2018), 2023)
At the 69th Statutory Meeting it was decided (C.Res.1981/2z27:5) that the Saithe (Coalfish) Working Group should meet at ICES headquarters20-27 April 1982 to:(i) assess catch options for saithe stocks in 1983. taking into account possible relationship between the North Sea stock and the North-East Arctic stock,(ii) assess catch options for cod and haddock in the Faroes area,(iii) advise on appropriate mesh sizes for saithe for trawl gears in Sub-areas land 11 and Sub-area IV,(iv) specify deficiencies in data required for assessments. ...